Cropland degradation and nutrient overload on Hainan Island: A review and synthesis. (15th November 2022) - Li, Tingyu; Hong, Xiuyang; Liu, Shuoran; Wu, Xiaoqiao; Fu, Shan; Liang, Ye; Li, Jinghua; Li, Ran; Zhang, Chong; Song, Xiaotong; Zhao, Hongwei; Wang, Dengfeng; et al.
Abstract: As the only "tropical base of agricultural production" in China, Hainan lsland is vigorously developing high-value agriculture and is becoming the province with the highest proportion of cash crops. However, this intensive farming with large nutrient inputs has caused cropland degradation, nitrogen (N) and phosphorus (P) overloads and water pollution, which have been reversed to initiate the construction of free trade ports. Here, we systematically review the status, driving factors, and environmental impacts of cropland degradation and nutrient overload with quantified evaluations and compared with other global tropics. Over the last 30 years, the soil pH in Hainan decreased by 0.3 units, and the soil organic carbon (SOC) decreased by 20%. This soil degradation has consequently aggravated nutrient losses, caused low use efficiency, and has required farmers add additional large nutrient to maintain harvests. P overuse is more serious than N overuse in Hainan due to the misuse of high P content compound fertilizers. The current N and P usage densities were 4% and 66% higher than the national average per crop season, i.e., 301 kg N ha −1 and 98 kg P ha −1, respectively, and the application rates were even higher for vegetables, i.e., 43% and 115% higher than the national average for vegetables. Consequently, water quality degradation occurred. The nutrient contents of several estuaries have exceeded the Class III standards. Potential improvement strategies are proposed: (i) Organic materials must be recycled to curb the declines in SOC and pH, and more benefits would be obtained by together use of biochar. (ii) Nutrient quotas must be implemented to balance nutrient budgets and reduce excessive surpluses and losses. (iii) The service functions of ecological protection zones for water and soil conservation must be strengthened. These strategies also apply to other global tropics that face similar challenges of soil and ecological degradation. Graphical abstract: Image 1 Highlights: Cropland degradation, nutrient overloads and water pollutionimpeded the construction of free trade ports of Hainan Island. Over the last 30 years, the soil pH decreased by 0.3 units and the soil organic carbon (SOC) decreased by 20% in Hainan. The current N and P usage densities were 4% and 66% higher than the national average per crop season. Potential improvement strategies and insights are proposed.